DEVELOPMENT OF MADURA TRADITIONAL CULINARY AS TOURISM AND CULTURAL TRADITIONS (STUDY OF PHENOMENOLOGY ON TRADITIONAL CULINARY SELLERS OF MADURESE SOCIETY) (International Conference on Social and Islamic Studies, 2021)
Madurese traditional cuisine is one of the developing cultures and has become a symbol of each region. Culinary may be the main attraction for others. In other words, culinary tourism is a tourist activity that highlights the characteristics or culinary delights as a tourist attraction. A typical food serves as a sign of an area and can distinguish its existence from other regions. Therefore, the researcher hopes to study the development of Madura's traditional culinary as a cultural heritage and tradition in more depth. Culinary existence has touched all aspects of life and is the cornerstone of every economy, marking social differences, boundaries, ties and contradictions. The interesting thing about food is the changing discourse about food itself. Changes in discourse that arise as a result of shifting views about food as a practical issue into an aesthetic problem. This study aims to explain concepts and solutions regarding culinary development on Madura Island as a cultural heritage and tradition with a focus on efforts to improve the culinary existence of Madura in the current era, thus making Madura as an island rich in its characteristics. culinary field so as to be able to compete at the international level. national and international. This effort will ultimately encourage the improvement of the quality of human resources on the island of Madura through Madura culinary entrepreneurship. This research will go through observation, in-depth interviews and documentation to obtain the desired data. Then this study uses the AGIL scheme from Talcott Parsons as the theoretical basis. Using primary and secondary data sources to support the completeness and validity of the data.